Changing clinical profile of malaria at a tertiary care hospital - Rathod, Shital N.; Chavan, Arvind; Sharma, Shilpa; Rathod, Tushar; Khan, Nihal; Bavdhankar, Koustubh (International Journal of Advances in Medicine, 2018)
Background: There is a widespread range of diverse typical and atypical manifestations of malaria. The diagnosis of malaria may escape the attention of treating physician due to its unusual and vague presentations.The morbidity and mortality due to malaria is increased due to lack of early diagnosis and right treatment. The Aim of the present study was to examine the changing clinical pattern of malaria with special attention to atypical presentations. Methods: The present study comprised of 630 cases of definitively diagnosed malaria.Diagnostic methods used were conventional thick and thin peripheral smear stained with Leishman stain and rapid malarial antigen test. Results: This study revealed atypical symptoms like lack of taste (1.3%), throat discomfort (13.33%) and cough (24.0%) and vomiting (52.4%) as presenting complaints. These were significantly more in patients with P. vivax infestations. Conclusions: A high degree of suspicion is necessary for early detection and treatment of malaria, especially of unusual presentations.